2008
DOI: 10.4137/cmo.s333
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Carcinoma with Bone Metastases: A Prognostic Factor Study

Abstract: Objective: Occult clinical presentations usually hinder the early detection and management of patients with bone metastases from thyroid carcinoma. We retrospectively investigated the clinical outcomes of such patients from 1993 to 2004 and analyzed the prognostic parameters. Design:The basic demographic data and manifestations of 44 patients who had thyroid carcinoma with bone metastases were reviewed. We studied the gender, age, locations of metastases, histological types, treatment methods, hypercalcemic ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 13 publications
4
34
1
Order By: Relevance
“…The only statistical difference between the two groups was that distant metastases, particularly bone and liver metastases, which are known to be a poor prognostic factor for survival (7,8,9,29), were much more frequent in patients with elevated levels of Ca 19.9 at the time of observation. However, in the present selected series, the distant metastases did not correlate with death while it did occur for Ca 19.9, suggesting a stronger prognostic role of this serum marker in this subset of advanced cases.…”
Section: Discussionmentioning
confidence: 88%
“…The only statistical difference between the two groups was that distant metastases, particularly bone and liver metastases, which are known to be a poor prognostic factor for survival (7,8,9,29), were much more frequent in patients with elevated levels of Ca 19.9 at the time of observation. However, in the present selected series, the distant metastases did not correlate with death while it did occur for Ca 19.9, suggesting a stronger prognostic role of this serum marker in this subset of advanced cases.…”
Section: Discussionmentioning
confidence: 88%
“…Wu et al (2008), who analyzed 44 patients of thyroid carcinoma with bone metastasis, showed that proper operations aiming at preventing or treating complications of metastatic bone disease appear to be useful in improving morbidity in patients with skeletal disease. Bernier et al (2001) retrospectively studied 109 DTC with bone metastasis, in which 24 (22%) patients were treated by complete excision of the metastasis, 60 (55%) patients were treated by partial removal, while others did not receive any surgery, with the median survival time being 6.2, 4.2, and 2.5 years, respectively (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relatively indolent behavior of encapsulated follicular thyroid neoplasm, the 5-year survival rate in patients detected with bony metastases in invasive FVPTC is reported to be 79.4% with 10-year survival rate being 52.9% [47].…”
Section: Resultsmentioning
confidence: 97%